EduTec Implementation in a global higher education network. Empirical data from a field study in South Asia - Vithanapathirana, M.; Jalilov, O.; Köhler, T.; Karunanayaka, S. P.; Hummel, S.; Sheehan, B. (GeNeMe Conference, Dresden, Germany, 2020)
This paper examines the appropriateness of using educational technologies toward increasing fexibility of learning in a global higher education in South Asia. The integration of information and communication technology (ICT) into education is widely perceived as an essential aspect of teaching and learning in contemporary society and therefore embodied in education policies across many countries, Cambodia and Sri Lanka included. Authors consider the argument that while interactive educational technologies may be appropriate in countries in which self-directed study and student autonomy are emphasised, a similar use of educational technologies may be found appropriate. Yet, in South Asian countries, education has traditionally been more tightly structured and teacher-directed that is why this paper does examine government policies toward the use of educational technologies in higher education in Cambodia and Sri Lanka. Qualitative analyses of both needs and challenges of introducing and implementing ICT in these particular cultural contexts are considered as preconditions for an efective implementation of Higher Education (HE) skill development. Subsequently, a plan is concluded of how to implement EdTec in that HE network to trigger awareness about further steps of the recent measure.
Keywords: education technology; 21st century skills; online learning environment; global higher education; ICT implementation